2008
DOI: 10.1016/j.ejpain.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered pain processing in children with migraine: An evoked potential study

Abstract: In adults, evidence is accumulating that migraine is associated with altered central processing of pain stimuli and, possibly, changes in the allocation of attentional resources to such stimuli. In pediatric migraine, however, little is known about altered pain processing. We examined 15 children with migraine and 15 controls (age 10-15) in an oddball standards task. Children had to respond to rare targets (tones) and ignore frequent painful (pain threshold) or non-painful mechanical standard stimuli while evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…Previous studies have reported lower pain threshold (PT) in children with chronic pain conditions, even in body areas not affected by disease 5,6,7,8,9 , supporting the theory that chronic pain conditions alter central nervous system pain perception and sensitization 10 .…”
mentioning
confidence: 94%
“…Previous studies have reported lower pain threshold (PT) in children with chronic pain conditions, even in body areas not affected by disease 5,6,7,8,9 , supporting the theory that chronic pain conditions alter central nervous system pain perception and sensitization 10 .…”
mentioning
confidence: 94%
“…The impact of early and repeated childhood pain on future pain experiences has been studied in several pediatric populations aside from sickle cell disease (SCD) 11, 20, 21, 25, 27, 37, 43, 4649, 54, 55, 57 . Pain sensitization in childhood is a complex phenomenon, dependent on the type of painful insult 2 , the developmental stage of the child 13 , and the child’s cumulative experience with pain 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond infancy, accumulating literature suggests that severe or frequent childhood pain can increase the risk for adult chronic pain 21, 2427 . Additionally, clinical literature suggests that children with chronic pain may exhibit increased pain sensitivity between attacks 57 as well as attentional bias to painful stimuli 55, 56 . With regard to pain from medical procedures, research also suggests greater sensitivity to procedural pain in younger versus older children 4, 13, 45, 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in clinical pediatric samples has found evidence of wind-up in children with complex regional pain syndrome (CRPS) [28], migraine [40], and abdominal pain [38]. Additionally, chronic pain during childhood predicts wind-up to heat pain in adult women [10].…”
Section: Emerging Methodologies and Novel Applicationsmentioning
confidence: 99%
“…Electroencephalogram (EEG) responses in children with migraines have been shown to have longer amplitude and shorter latency compared to healthy youth during a QST perceptual sensitization task [38], suggesting youth with pain conditions may demonstrate an attentional bias to pain. Another study examining cortical responses in youth with abdominal pain achieved similar results [19].…”
Section: Emerging Methodologies and Novel Applicationsmentioning
confidence: 99%